Practice and effectiveness of guidance and counseling in Nepali schools: roles of learning strategy, self-management, and social skills - Khadka, Jiban; Dahal, Niroj; Hasan, Md. Kamrul; Haque, Md. Nurul; Joshi, Dirgha Raj; Subedi, Nirmala; Acharya, Usha (Frontiers in Education, 2025)
This study investigates the status and effectiveness of guidance and counseling (G&C) practices in Nepali schools, focusing on three domains: learning strategies (LS), self-management (SM), and social skills (SS). Through a quantitative survey of 384 teachers, counselors, and headteachers across seven provinces of Nepal, we assessed G&C practices using a validated 30-item questionnaire adapted from the American School Counselor Association (ASCA) 2021 standards. We evaluated four school performance indicators—school environment, student behavior (e.g., social/emotional conduct), academic achievement, and post-school success—using teacher-reported 3-point scales (i.e., Good, Normal, and Needs Improvement). Using binary logistic regression, we tested four hypotheses. We found that SS were a strong predictor of better student behavior [odds ratio (OR) = 2.371, p < 0.05], as evidenced by fewer conflicts and better ethical behavior. Infrastructure (dedicated counseling rooms: OR = 2.838) and trained counselors (OR = 2.929) strongly enhanced school environments. LS and SM interventions did not have a significant impact on academic outcomes (e.g., test scores, dropout rates). Critical gaps include inadequate training in LS/SM strategies (e.g., only 9.6% of schools had counselors; teachers struggled with goal-setting and coping skills guidance). The findings emphasize the importance of conducting teacher workshops focused on delivering Learning Support and Student Mentoring (LS/SM). Additionally, there is a need for institutional support to improve counseling infrastructure and to integrate structured G&C frameworks. This study offers practical suggestions, such as creating specific areas for counseling and setting up uniform training programs to improve G&C services in places with limited resources.